THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND CAPITAL INTENSITY ON TAX AVOIDANCE IN CONSUMER GOODS INDUSTRY SECTOR LISTED IN INDONESIAN STOCK EXCHANGE - Dyah Pelitawati; Ony Kurniawati, Monica Andriani (Adisam Publisher, 2024)
Tax avoidance is an act of reducing company tax which is legal if it follows the applicable tax provisions. The aim of this research is to determine and analyze the partial and simultaneous influence of profitability, liquidity and capital intensity on tax avoidance in consumer goods industry sector companies listed on the Indonesian stock exchange for the 2019-2021 period. The research method used is a quantitative method, using secondary data in the form of company financial reports. Using a purposive sampling method, 19 financial reports from the consumer goods industry sector listed on the Indonesian stock exchange were selected in the 2019-2021 observation year. The analysis was carried out using the SPSS for Windows version 25 program, through a set of multiple linear regression analysis tests and partial and simultaneous hypothesis tests. The results in this research show that partially the profitability variable and liquidity variable have no effect on tax avoidance, and only the capital intensity variable has an effect on tax avoidance. Simultaneously, the variables profitability, liquidity and capital intensity influence tax avoidance in consumer goods industry sector companies listed on the Indonesian Stock Exchange.